Functionalized Coumarine Fragment to Obtain Fluorescent and Selective P‐Glycoprotein Ligands. Issue 3 (11th January 2016) - Capparelli, Elena; Contino, Marialessandra; Perrone, Maria G.; Berardi, Francesco; Perrone, Roberto; Leopoldo, Marcello; Colabufo, Nicola A.
Abstract : Starting from our lead compoundMC70 displaying high P‐glycoprotein (P‐gp) inhibition activity but low selectivity, a new class of coumarine derivatives was studied to develop selective and fluorescent P‐gp ligands. In this series, the biphenyl moiety ofMC70 was replaced with the coumarine fluorophore as a bioisostere of the biphenyl nucleus in order to improve the selectivity toward P‐gp and the fluorescent properties for in vitro studies. Moreover, the presence and position of substituents on the coumarine nucleus were probed to develop suitable fluorescent probes to study the expression and activity of P‐gp in living cells. The best result was found for compound4c, which exerts a good P‐gp activity profile (EC50 = 13 μM) as substrate and a high selectivity toward the pump since it is inactive toward MRP1. Abstract : A new class of P‐glycoprotein ligands bearing a fluorescent moiety (coumarine) linked to a nucleus responsible for the interaction with the pump (isoquinoline fragment) was developed. Among these ligands, compound4c (EC50 = 13 µM) displayed suitable fluorescent properties for in vitro studies.